1, 4‐Migration of Transition Metals in Organic Synthesis. Issue 9 (31st July 2019) - Rahim, Abdur; Feng, Jia; Gu, Zhenhua
Abstract : Generation of carbon‐metal species is extremely important in transition metal‐catalyzed organic synthesis. Among the various methods, 1, 4‐metal migration is a very useful way to create new carbon‐metal species, which are not readily accessible via classic methods. This review summarized recent advances in transition metal‐catalyzed reactions, which involved one or more steps of 1, 4‐metal migration. It focused mostly on the achievements in Pd and Rh‐catalyzed reactions, along with some of the remarkable results in Pt, Ir, Co, Fe‐involved transformations. Abstract : The 1, 4‐metal migration is a very useful way to create new carbon‐metal species, which are pivotal in transition metal‐catalyzed transformations. This review summarized the recent advances in transition metal‐catalyzed reactions, which at least contained one step of 1, 4‐metal migration.